Non-contact 3D acquisition system based on stereo vision and laser triangulation - Vilaça, João L. (2010)
This paper proposes a novel contact 3D acquisition system based on stereo vision and laser triangulation. The system is composed by several software modules for data acquisition purposes, data calibration, data processing and data reconstruction of 3D scenes. Different 3D image techniques, such as, polynomial determination, cubic spline interpolation and hierarchical space decomposition were used. To validate this method, a simple laboratory prototype machine was built for the purpose of road proﬁle acquisition, road macro and mega texture characterization. In this paper, only the results and discussion of road proﬁle acquisition are presented.